RESILIENSI PENDIDIK PAUD DI KECAMATAN SEMIN, KABUPATEN GUNUNG KIDUL - Endin Wicaksono; Titik Muti’ah (Universitas Sarjanawiyata Tamansiswa, 2015)
AbstrackThe aim of this research is to know how far is the resiliency of the pre school educator in Semin, Gunungkidul. The subyect of this research are four educators of pre school in Semin, Gunungkidul. The data analysis method that is used in this research are used in this research are data collection, data reduction, triangulation and conclusion.The result of the data analysis can be conduded that there are two aspects which are found in 17 categories of the pre school educators resiliensi variabel in order to develop the pre school in Semin, Gunungkidul. The aspects are resiliensy of capability and 34 sub categories. And the second aspect is the characteristic resiliency which has 18 sub categories that influence the resiliency.Â Keywords : Resiliency, pre school educator.